Social Mobility In Daniel Defoe's Moll Flanders (1722):A Marxist Approach - Afrelia, Prehatin; , Dr. M Thoyibi, M.S; , Nur Hidayat, M.Pd (2016)
This study is about social mobility in Moll Flanders (1722) by Daniel Defoe. It is analyzed by using Marxist approach which is proposed by Karl Marx. The objectives of this study are to find out the indicators of individual's social mobility in society, the depictions of the process of social mobility in society, and the author concern towards the existence of social mobility. This research is categorized into qualitative research. The primary data of this study is Moll Flanders (1722) by Daniel Defoe and the biography of the author. The secondary data of this study is taken from, literary books, websites and the other sources that related to the issue of social mobility. There are three conclusions which can be drawn from this study. Firstly, there are three indicators that indicate social mobility; education attainment, the parts of income, and wealth. Secondly, the process of social mobility is depicted into four steps; being a servant, marriage misuse, being a thief, and being the plantation owner. Thirdly, Daniel Defoe concern toward social mobility issue is that he wants to reveal the existence of achievement of bourgeoisie woman in capitalist society. Keywords: social mobility, Moll Flanders, Bourgeoisie, Proletariat, Marxism